Pembrolizumab plus chemotherapy in metastatic non-small-cell lung cancer - Gandhi, Leena; Bischoff, Helge (The New England journal of medicine, 2018)
Addition of Immunotherapy in Lung Cancer The addition of pembrolizumab to chemotherapy for metastatic lung cancer without EGFR or ALK mutations resulted in better progression-free and overall survival than chemotherapy alone. Immune-related adverse effects were more common with the combination.
Gesehen am 13.12.2019